2017
DOI: 10.1371/journal.pone.0174984
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome analysis of the excretory tubules of Carausius morosus (Phasmatodea) and possible functions of the midgut ‘appendices’

Abstract: The Malpighian tubules are the insect excretory organs, responsible for ion and water homeostasis and elimination of nitrogenous wastes. Post-genomic assays suggest they also metabolize and detoxify xenobiotic compounds and have antimicrobial properties. The Phasmatodea have an additional, unique set of excretory organs referred to predominantly as midgut appendices. Their function and how it compares to phasmid and other insect Malpighian tubules is unknown. Hypotheses include carbonic anhydrase activity, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…stephensi are expressed in fat body, midgut, haemolymph and salivary glands with the high level of expression at fat body 49 . On the contrary, a defensin gene from Bemisia tabaci was more highly expressed in adult midgut or salivary glands than in fat bodies 52 and a type of attacin gene was highly expressed in adult Malpighian tubules of the stick insect Carausius morosus 53 . It was also reported constitutive expression of a termicin gene in adult haemolymph and salivary glands from the termite P. spiniger 32 .…”
Section: Discussionmentioning
confidence: 95%
“…stephensi are expressed in fat body, midgut, haemolymph and salivary glands with the high level of expression at fat body 49 . On the contrary, a defensin gene from Bemisia tabaci was more highly expressed in adult midgut or salivary glands than in fat bodies 52 and a type of attacin gene was highly expressed in adult Malpighian tubules of the stick insect Carausius morosus 53 . It was also reported constitutive expression of a termicin gene in adult haemolymph and salivary glands from the termite P. spiniger 32 .…”
Section: Discussionmentioning
confidence: 95%
“…Correlations between the transcriptomes in many tissues or organs of animals (e.g., antennae, salivary glands, midgut, midgut ‘appendices’, hepatopancreas, venom gland, gill) and its respective physiological functions have been reported [ 40 45 ]. Similar studies have been carried out for the MTs of a few insect species, but these studies have been limited in viewing the MTs as a whole organ [ 3 , 5 , 10 , 12 , 22 , 25 , 46 50 ]. To our knowledge, studies of the transcriptome of vector leafhoppers have mainly focused on the salivary glands and the alimentary tract [ 51 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the salivary glands and alimentary tract of vector leafhoppers have the ability in the metabolism of natural and synthetic xenobiotics/toxins by expressing a variety of detoxification enzymes [ 51 – 53 ]. Previous studies also suggest that MTs of phytophagous insects display the abundance of enzymes related to detoxification of plant defense compounds, insecticides and other xenobiotic compounds [ 3 , 5 , 8 , 10 , 21 , 22 , 46 , 49 , 50 , 64 ], making the tubules a major site of insecticide detoxification and resistance [ 49 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences are listed in Supporting Information S1 and S2, which also consider partial sequences (+). Additionally, obtained sequences with allelic differences, sequences completed from RAW data and publicly available databases33 are indicated by "*". TSA, transcriptome shotgun assembly; SRA, sequence read archive; t , unpublished Trinity assembly; b , unpublished Bridger assembly.…”
mentioning
confidence: 99%